1984
DOI: 10.1007/bf01641017
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseri as the cause of septic urinary infection

Abstract: A 66-year-old patient developed severe urinary stasis due to a concrement in his right ureter; foudroyant septicemia followed. Lactobacillus gasseri was grown from pyoid urine from the right renal pelvis and in two blood cultures, thus suggesting septic urinary infection caused by lactobacilli. The infection was cured by catheterisation of right ureter and antibiotic treatment with cefotaxime and amoxicillin. The concrement was removed by dissolution. Diabetes and urinary stasis appear to be the main predispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Recent studies showed that the urine microbiota consists mainly of lactobacilli (29,30); therefore, the organisms isolated from UG samples in this study likely represent commensal organisms. However, Lactobacillus has been associated with urinary infections in the literature (31) and was associated with a UTI with obstruction in one of our patients (L. rhamnosus in the urine of a male patient). A limitation of our study is that it was conducted within a primarily adult male population.…”
Section: Discussionmentioning
confidence: 69%
“…Recent studies showed that the urine microbiota consists mainly of lactobacilli (29,30); therefore, the organisms isolated from UG samples in this study likely represent commensal organisms. However, Lactobacillus has been associated with urinary infections in the literature (31) and was associated with a UTI with obstruction in one of our patients (L. rhamnosus in the urine of a male patient). A limitation of our study is that it was conducted within a primarily adult male population.…”
Section: Discussionmentioning
confidence: 69%
“…Our review of the literature revealed only one previously published case report of a 66-year-old diabetic male who developed acute renal failure and sepsis in a setting of ureteral obstruction. The patient's urine and blood yielded pure cultures of Lactobacillus gasseri, and following treatment with amoxicillin, the patient recovered fully (3).…”
mentioning
confidence: 95%
“…Infections by Lactobacillus gasseri are rarely reported in the literature. A case of Fournier gangrene [2], urinary tract infection [11], and polymicrobial empyema [7] were previously reported. In this case, we present the first monomicrobial Lactobacillus gasseri bilateral empyema that was successfully treated by video-assisted thoracoscopic surgery along with chest tube placement and drainage.…”
Section: Discussionmentioning
confidence: 99%